ANALISIS RESOLUSI KONFLIK LAHAN PERTANIAN DI SEKITAR PERTAMBANGAN NIKEL DI KECAMATAN WAWONII TENGGARA KABUPATEN KONAWE KEPULAUAN - Preslei, Randi; Sidu, Dasmin; Mardin, Mardin (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2024)
The growth of mining companies in Konawe Islands is certainly inseparable from community rejection. The purpose of this study is to: determine and analyze the types, causes, and resolution of conflicts between mining companies and the community on agricultural land in Roko-Roko Village, Southeast Wawonii District, which have the potential for conflict between the Company and the community. The informants used in this research are: farmers, village government, sub-district government, police, and NGOs. The selection of informants was carried out deliberately with the consideration that the informants reside and/or work at the research location, know and understand information related to the conflict at the research location. This research uses primary and secondary data which are analyzed descriptively with the results, namely: the types of conflicts that occur between companies and the community are individual conflicts and conflicts between social classes. Then the cause of individual conflict is differences in interests, while between social classes is caused by violations of rights and territorial disputes. Until finally the resolution of individual conflicts uses the conciliation method, while between social classes uses the mediation method.